The carbon emissions of selected airlines and aircraft types in three geographic markets - Miyoshi, Chikage; Mason, Keith J. (Elsevier Science B.V., Amsterdam., 2009)
Various carbon calculators developed by airlines and carbon offset companies have become available since the environmental impact of the air transport industry started to receive strong attention. This paper details a prototype methodology for carbon calculation emission levels in the three air transport markets; the UK domestic routes, the intra-EU routes serving UK and the North Atlantic routes that enables the assessment of key environmental performance differences between air carriers whereas they would be measured as identical using the often used DEFRA-type measurement approach. The results show differences in airlines' strategies such as aircraft type used, load factors and seat configurations.
Keywords: Environment; Carbon calculator methodology; Business travel; Airline business models